Transdisciplinarity and Shifting Network Boundaries: The Challenges of Studying an Evolving Stakeholder Network in Participatory Settings. Issue 4 (November 2021) - Prell, Christina; Hesed, Christine D. Miller; Johnson, Katherine; Paolisso, Michael; Teodoro, Jose Daniel; Van Dolah, Elizabeth
Participatory research engages a transdisciplinary team of stakeholders in all aspects of the research process. Such engagement can lead to shifts in the research design, as well as who is considered a participant. We detail our experiences of studying an evolving stakeholder network in the context of a 2.5-year transdisciplinary, participatory project. We show how participation leads to shifts in the network boundary overtime and how a transdisciplinary effort was needed to retrospectively redefine the network boundary. Through tacking back and forth between ethnographic insights, research aims, and modeling assumptions, the team eventually reached agreement on what determined network membership and how to code network members according to their timing and level of participation. Our account advances literature on boundary and modeling approaches to shifting, evolving networks by demonstrating how participatory transdisciplinarity can be both a driver of, and solution to, capturing the complexity of evolving networks.